Counterrevolution the global rise of the Far right - Bello, Walden F. (Ateneo de Manila University Press, 2019)
The far right is on the rise. The rhetoric of anger and resentment of political leaders like Donald Trump, Marine Le Pen, Rodrigo Duterte, and Narendra Modi is captivating and mobilizing large numbers of people. In an increasing number of countries, the extreme right has already captured the government or is on the threshold of power. In Counterrevolution, harnessing the methods of comparative history and comparative sociology, Walden Bello deconstructs the challenge from the extreme right across the globe by deploying what he calls the dialectic of revolution and counterrevolution.-- Back cover.